Non-surgical treatment of hidradenitis suppurativa: the role of cryotherapy - Dell'Antonia, Massimo; Anedda, Jasmine; Tatti, Alice; Falco, Alessandro; Sanna, Silvia; Ferreli, Caterina; Atzori, Laura (Frontiers in Medicine, 2023)
Background: Hidradenitis suppurativa is a chronic and recurrent inflammatory disease with a great impact on patients’ quality of life, due to the painful involvement of very sensitive areas, such as the groin, mammary area and genitals, with malodourous discharge. Multiple treatments options are available; however, no single treatment is effective for all patients, and usually a combination of medical therapy with various surgical and physical procedures is provided. Cryotherapy is not a routinely technique to treat HS, although usually available in the majority of medical clinics, and cheaper than laser and surgical treatments. Aim of this study is to evaluate the effectiveness of cryotherapy on persistent HS nodules, to reduce the burden of local disease. Materials and methods: retrospective observational study in all patients treated with liquid nitrogen cryotherapy for persistent nodules of hidradenitis suppurativa in the last 2 years, with at least 6 months of follow-up after the procedure. Disease severity was assessed with Hurley staging and sonographic staging according to SOS-HS (18 MHz probe, Esaote-MyLab™). Results were scored with a 0-3 points scale, as complete remission (3), partial response (2 to 1) or no response (0), after one session of treatment. Local cleansing and antiseptic treatment after the procedure was the same previously performed in each patient, not to influence recovery. Results: 23 patients were included, with a total of 71 persistent nodules treated with a single cryotherapy session. The treatment has been effective in 63 out of 71 nodules treated (88,7%), and the patients attested they recommend the treatment, the discomfort during recovery was minimal and the management not different from daily routine. Persistence was considered as failure rate (11,3% overall), and occurred in 7,5% of the nodules of the axillary region, 18,2% on the groin and 11,2% for nodules of the gluteal region. Conclusion: cryotherapy is a simple and effective procedure for the treatment of persistent nodules of HS not responding to medical therapy, it is a valid alternative to local surgery or laser ablation.